The Effectiveness of Case Study-Based Hybrid Learning on Students' Problem Solving Ability Based on MIA - Agoestanto, Arief; Rochmad, Rochmad; Azmi, Kholifatu Ulil; Octalia, Rembulan Permata (UNNES JOURNAL, 2024)
Problem solving skills must be familiar to students in any condition. However, during the pandemic, students have not optimally mastered this ability. At the end of the pandemic, case study-based hybrid learning is highly recommended in higher education. The objective of this research is to analyze the effectiveness of case study-based hybrid learning on problem solving skills which are detailed: (1) analyzing the completeness of students' problem solving ability of case study-based hybrid learning classically, (2) analyzing the completeness of students' problem solving ability of case study-based hybrid learning based on Mathematics Initial Ability (MIA), (3) analyzing the difference in the completeness of students' problem solving ability of case study-based hybrid learning with problem-based hybrid learning, (4) analyzing the difference in students' problem solving ability of case study-based hybrid learning with problem-based hybrid learning based on MIA. This quantitative research took 6th-semester students of the Mathematics Education Study Program of Universitas Negeri Semarang who took the Statistics of Education course in the 2021/2022 academic year as the population. Of the 6 class, 2 class were selected as samples, by random sampling. The research design used a post-only control design. How to collect data with a problem solving ability test. Data were analyzed using the z-test, and independent t-test. From the research obtained the results (1) the problem solving ability of students of Hybrid learning based on case study problems is classically complete both by mean and proportion, (2) students with high MIA, and medium, are complete by mean and proportion, while students with low MIA have not completed by mean and proportion, (3) there is no difference in the completeness of the problem solving ability of students of hybrid learning based on case study problems with hybrid learning based on problems, (4) there is a difference in the problem solving ability of medium MIA, there is no difference in low and high MIA in both learning models. Kemampuan pemecahan masalah harus dibiasakan bagi mahasiswa dalam kondisi apapun. Namun pada masa pandemi, mahasiswa belum secara maksimal menguasai kemampuan tersebut. Di masa pandemi berakhir, pembelajaran hybrid berbasis studi kasus sangat dianjurkan di perguruan tinggi. Tujuan penelitian ini adalah untuk menganalisis efektivitas pembelajaran hybrid berbasis studi kasus terhadap kemampuan pemecahan masalah yang dirinci: (1) menganalisis ketuntasan kemampuan pemecahan masalah mahasiswa pada pembelajaran hybrid berbasis studi kasus secara klasikal, (2) menganalisis ketuntasan kemampuan pemecahan masalah mahasiswa pada pembelajaran hybrid berbasis studi kasus berdasarkan Kemampuan Awal Matematika (KAM), (3) menganalisis perbedaan ketuntasan kemampuan pemecahan masalah mahasiswa pada pembelajaran hybrid berbasis studi kasus dengan pembelajaran hybrid berbasis masalah, (4) menganalisis perbedaan kemampuan pemecahan masalah mahasiswa pada pembelajaran hybrid berbasis studi kasus dengan pembelajaran hybrid berbasis masalah berdasar KAM. Penelitian kuantitatif ini mengambil mahasiswa semester 6 Program Studi Pendidikan Matematika Universitas Negeri Semarang yang mengambil mata kuliah Statistika Pendidikan tahun ajaran 2021/2022 sebagai populasinya. Dari 6 kelas dipilih 2 kelas sebagai sampel, dengan cara random sampling. Desain penelitian menggunakan post-only control design. Cara pengambilan data dengan tes kemampuan pemecahan masalah. Data dianalisis menggunakan uji z, dan uji t independen. Dari penelitian diperoleh hasil (1) kemampuan pemecahan masalah mahasiswa pada pembelajaran Hybrid berbasis permasalahan studi kasus tuntas secara klasikal baik mean maupun proporsinya, (2) mahasiswa dengan KAM tinggi dan sedang tuntas secara mean dan proporsinya, sedangkan mahasiswa dengan KAM rendah belum tuntas secara mean dan proporsi, (3) tidak terdapat perbedaan ketuntasan kemampuan pemecahan masalah mahasiswa yang pembelajaran hybrid berbasis masalah studi kasus dengan pembelajaran hybrid berbasis masalah, (4) terdapat perbedaan kemampuan pemecahan masalah KAM sedang, tidak terdapat perbedaan KAM rendah dan tinggi pada kedua model pembelajaran.